Reducing Violent Behavior in Schizophrenia Patients using Happy Spiritual Intervention through Rufa Caring System Monitoring - Dwidiyanti, Meidiana; Wijayanti, Diyan Yuli; Munif, Badrul; Kandar, Kandar; Suerni, Titik (Nursing Information Journal, 2025)
Competent psychiatric nurses are required to be capable of treating schizophrenia patients so that they can behave adaptively. This study aimed to determine differences in violent behavior among patients with schizophrenia before and after the happy spiritual intervention through the RUFA Caring System. The research employed a pre-experimental study with a pre-post-test without a control group design was conducted among 50 schizophrenia patients in stable wards. The sample in this research is schizophrenia patients who were diagnosed with violent behavior and able to communicate and were purposively recruited. The happy spiritual intervention was given four times for 30 minutes each. Data on violent behavior were collected using the RUFA (General Response of Adaptive Function) scale presented in the RUFA caring system application. The paired t-test was used for data analysis. The mean ± SD of the RUFA caring system score was (29.0±3.4) and (19.3±8.7), before and after the intervention, respectively. The paired t-test analysis found a decreased score of 10.3±5.3 with a p-value of 0.000 (p<0.005) and an effect size of 1.94 (d>0.8). Happy spiritual intervention through the RUFA Caring System is highly effective for mentally disordered patients to control their emotions so that they can reduce violent behavior.